PENGARUH KEPEMIMPINAN DAN KOMPETENSI TERHADAP KINERJA PEGAWAI KANTOR KECAMATAN PANCORANKOTA ADMINISTRASI JAKARTA SELATAN - Syopwani . (Prima Center Indonesia, 2017)
This study aimed to determine the effect of leadership and competence to employee performance Pancoran sub-district office administrative capital city of Jakarta Selatan.Penelitian this is a kind of research usingquantitative research methods. The population in this study were employees of the district and some villages employee se Pancoran sub-district with a sample of 100 people. Processing data using statistical techniques using the workings of correlation analysis, determination and statistical hypothesis testing simple regression and multiple regression statistical and correlation kofesien, all of which are in the program by using SPSS software. The results of this study indicate that there are significant positive and significant of leadership variable camat (X1) on employee performance (Y) rX1Y = 0.647., And there is a positive and significant effect of the variable employee competence (x2) with employee performance (Y) with rX2Y = 0.595, there is also a positive and significant influence between the variables of leadership camat (X1) with the competence of employees (X2) that rX1X2 = 0.566, and thus based on the examination of the research results, it can be concluded that the overall hypothesis proposed in this study tested and acceptable.Keywords: leadership, competence, and performance